PERANCANGAN KOMPOSISI BAHAN SAMI MENGGUNAKAN SERUTAN KARET BAN BEKAS - Ngii, Edward; Suparma, Latif Budi (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Using shredded rubber in SAMI mixture should be designed to obtain the aggregate structure that had a locks each other optimally. The research aimed to obtain the composition of SAMI material that design by shredded rubber in the mixture. Dry compaction test was performed to the mortar mixture to obtain the optimum composition of sand-filler. Two kind of filler were investigated were stone dust and cement portland. Analysis of density and porosity mortar were performed to obtain the target porosity that was used in the calculation of SAMI composition in the following proportion: 0%, 5%, 10% and 20% of shredded rubber by 0%, 5%, 10% and 20%. The results indicated that the optimum value of stone dust or cement filler in mortar mix by 30%. Use of stone dust filler 40% can produce the porosity value better than cement filler mortar, but this percentage need to be evaluated because design by high level filler cause the mixture of SAMI tends to brittle and easy to crack.